How Can We Statistically Analyze the Achievement of Diagrammatic Competency from High School Regular Tests? - Uesaka, Yuri; Saso, Shun; Akisawa, Takeshi (Diagrammatic Representation and Inference, 2021)
Owing to the recent global changes in education goals, students nowadays need to achieve ‘key competencies’ in school. ‘Diagrammatic competency’ is an essential part of such competencies. To cultivate diagrammatic competency, it is necessary to evaluate teachers and students and provide feedback on the students’ degree of achieving diagrammatic competency. Regular school tests can provide useful opportunities for assessing such achievement. However, in such tests, Japanese high schools mainly focus on evaluating the understanding of learning contents rather than the development of competencies (such as diagrammatic competency). The current study was a collaboration between educational psychologists and a high school mathematics teacher. Together they modified a regular school test to incorporate tasks that require diagrammatic competency to solve them, thus enabling the assessment of such achievement. The study was conducted in an actual high school. The students’ performance was analyzed using cognitive diagnostic models [1], which statistically estimate how well students have mastered the elements of cognitive abilities and skills required to solve problems, generating ‘attribute mastery probabilities’. The attribute mastery probabilities obtained demonstrated that students’ achievement of diagrammatic competency was insufficient, indicating a need for cultivating such competency in subject learning instruction provided in schools.